"Looking Mexican": Indigenous and non-Indigenous Latina/o Immigrants and the Racialization of Illegality in the Midwest. (3rd December 2019) - Gómez Cervantes, Andrea
Abstract: Immigration laws, judiciary hearings, and enforcement strategies produce the racialization of illegality, linking "illegality" to homogenized and stereotypical images of "Mexican, " "Hispanic, " and "Latina/o" origin. Immigration scholars have shown the transgressions produced by the racialization of illegality on Latina/o immigrants and non-immigrants who fit these stereotypes. How do Latina/o immigrants of different ethnic origins navigate the racialization of illegality? What strategies do they employ to manage risks associated with illegality? Through 61 interviews with Indigenous-origin and non-Indigenous Latina/o immigrants in Kansas between 2016 to 2019, this study examines the salience of race and the active role that the body plays within Latina/o immigrants' experiences with the immigration regime. I find that immigrants actively employ the body as a resource to navigate illegality, particularly in a context where Latina/os make up a smaller share of a white-majority population. The racialization of illegality brings social divisions within Latina/o groups, reproducing centuries-old systems of oppression where whiteness is equated with protections given to citizens, while "looking Mexican" or "Hispanic" leaves Indigenous-origin immigrants and non-white Latina/os at the hands of immigration control. This research contributes to scholars' call to further explore the role of race and the body in immigration processes.